2011
DOI: 10.1002/ptr.3385
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic Effect of Oleanolic Acid: A Promising Use of a Traditional Pharmacological Agent

Abstract: Diabetes mellitus (DM) is a metabolic disorder characterized by chronic hyperglycemia. Although the clear mechanisms of DM and insulin resistance are still to be cleared, it has been well documented that reactive oxygen species (ROS) play a pivotal role in DM and multiple types of insulin resistance. For the past few years, natural substances have been shown to have the potential to treatment DM. Attention has been especially focused on plants rich in triterpenoids, which generally show antioxidant and antigly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
56
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 31 publications
7
56
0
1
Order By: Relevance
“…In this paper, we present results proving that OA is not an α-amylase inhibitor. This finding is in agreement with other published data (Hou et al, 2009;Wang et al, 2011) although there are also contradictory results supporting that OA might effectively repress this activity (Khati et al, 2013;Ali et al, 2006;Komaki et al, 2003), with quite variable IC 50 values in the range of 10 ”M-2.6 mM.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this paper, we present results proving that OA is not an α-amylase inhibitor. This finding is in agreement with other published data (Hou et al, 2009;Wang et al, 2011) although there are also contradictory results supporting that OA might effectively repress this activity (Khati et al, 2013;Ali et al, 2006;Komaki et al, 2003), with quite variable IC 50 values in the range of 10 ”M-2.6 mM.…”
Section: Discussionsupporting
confidence: 93%
“…Its ability to react with diverse radical species has been evaluated, having obtained an array of varied results (Yin and Chan, 2007;Yang et al, 2007;Wang et al, 2010;Allouche et al, 2011). The OA effect on α-amylase is not completely clear (Khati et al, 2013;Wang et al, 2011). However, a consensus does exist concerning the efficient inhibition of α-glucosidase by the triterpene, and some IC 50 values in the micro-molar range have been reported (Ali et al, 2002;Kang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…visartiside A, visartiside B and eriodictyol 7-O-b-D-glucopyranoside, showed significant free radical scavenging activity with ED 50 values of 37.6, 34.1 and 63.3 lM, respectively. The study reported that these three flavanones possessed a 3 0 ,4 0 -dihydroxyphenyl group in the B-ring and suggested that [75][76][77]80,86] Antidiabetic, antituberculosis, diuretic, antitumour, cytoprotective, antioxidant, hepatoprotective, antihyperlipidaemic, antihypertension [78,[93][94][95][96][97][98] Betulinic acid N/A Anti-HIV, antibacterial, antimalarial, anti-inflammatory, anthelmintic, antinociceptive, anti-HSV-1, anticancer, antimalarial [97,99,100] Visartiside A Antioxidative, anti-inflammatory, cytotoxic [55] N/A Visartiside B Antioxidative, anti-inflammatory, cytotoxic [55] N/A Visartiside C Anti-inflammatory [55] N/A Visartiside D Anti-inflammatory [55] N/A Visartiside E Anti-inflammatory 55 N/A Visartiside F Anti-inflammatory [55] N/A Viscolin 4''-glucoside Anti-inflammatory…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…OA is structurally similar to CA, and is contained in several foods and medicinal plants, and possesses various biological properties, including anti-diabetic, anti-bacterial and anti-oxidative activities (14,15). In this study, we examined the effect of oleanolic acid (OA), a major oleanane-type trterpenoid, on macrophage polarization and glioblastoma cell proliferation in order to identify additional potentially useful candidate anti-cancer agents other than CA.…”
Section: Introductionmentioning
confidence: 99%